Influence of ATII blockers and calcium channel blockers on renal vascular resistance in patients with essential hypertension - Delić-Brkljačić, Diana; Galešić, Krešimir; Ivanac, Gordana; Manola, Šime; Pintarić, Hrvoje, liječnik; Štambuk, Krešimir; Gaćina, Petar; Radeljić, Vjekoslav (2009)
Abstract: Doppler can evaluate renal vascular resistance, and resistance index (RI) highly correlates with blood pressure and renal function in various pathological conditions. Purpose of the study was to measure and compare renal Doppler indices in patients with newly-diagnosed essential hypertension (EH) and in healthy subjects; to determine changes of Doppler indices in patients after six-months monotherapy with either the AT II blocker (valsartane) or calcium channel blocker (niphedipine); to determine which drug has better renoprotective effect. 65 healthy controls were examined, as well as 69 patients with the newly-diagnosed EH, without signs of the target organ damage. Duplex Doppler US of interlobar intrarenal arteries was performed, and RI, acceleration index (AI) and acceleration time (AT) measured. Antihypertensive monotherapy was performed with vaslartane in 34 patients and with niphedipine in 35 patients. Doppler was repeated after the six-months therapy.
RI in patients with the 1. stage of EH is significantly higher compared to the controls (p<0.001), and significantly lower compared to the stage 2. of EH (p<0.001). The significant decrease of systolic (p<0.001) and dyastolic blood pressure (BP) (p<0.001) was noted after the therapy. RI in healthy examinees (RI=0.59±0.023) is significantly lower than in EH (RI=0.66±0.26) (p<0.001), while AI is significantly higher (p<0.001), and AT is significantly lower (p<0.001). In patients treated with valsartane and those treated with niphedipine, the RIs are significantly lower than before (p<0.001), while AIs were significantly higher, and ATs were significantly lower after the therapy after the therapy with both drugs. RIs in patients treated with valsartane (RI = 0.615 ± 0.036) are significantly lower than RIs of patients treated with niphedipine (RI=0.642±0.030) (p<0.01) after therapy.
Regression analysis for the predictive values of RI, AT, AI in relation to the age-standardized values of systolic and diastolic BP of healthy examinees and patients with hypertension has demonstrated that RI is the strongest and statistically significant predictor in all groups of examinees. Six-months monotherapy of EH with valsartane or with niphedipine is equally efficient in the decrease of the blood pressure, but valsartane has more favourable effect on kidney. Resistance index measured in intrarenal arteries is the best parameter of Doppler spectrum in the evaluation of the effects of antihypertensive therapy on the kidney
Bibliografija: 37 jed
Sažetak
Keywords: Esencijalna hipertenzija -- AT II blokator -- Indeks otpora -- Akceleracijski indeks -- Akceleracijsko vrijeme